Sucralose Non-Carcinogenicity: A Review of the Scientific and Regulatory Rationale. (16th November 2016) - Berry, Colin; Brusick, David; Cohen, Samuel M.; Hardisty, Jerry F.; Grotz, V. Lee; Williams, Gary M.
ABSTRACT: Regulatory authorities worldwide have found the nonnutritive sweetener, sucralose, to be noncarcinogenic, based on a range of studies. A review of these and other studies found through a comprehensive search of electronic databases, using appropriate key terms, was conducted and results of that review are reported here. An overview of the types of studies relied upon by regulatory agencies to assess carcinogenicity potential is also provided as context. Physiochemical and pharmacokinetic/toxicokinetic studies confirm stability under conditions of use and reveal no metabolites of carcinogenic potential. In vitro and in vivo assays reveal no confirmed genotoxic activity. Long-term carcinogenicity studies in animal models provide no evidence of carcinogenic potential for sucralose. In studies in healthy adults, sucralose was well-tolerated and without evidence of toxicity or other changes that might suggest a potential for carcinogenic effects. In summary, sucralose does not demonstrate carcinogenic activity even when exposure levels are several orders of magnitude greater than the range of anticipated daily ingestion levels.